Hubungan Aktivitas Fisik Dengan Status Gizi Remaja Putri Di Pondok Pesantren Ta'mirul Islam Surakarta - Khasanah, Daimatul, Endang Nur W, SST., M.Si Med, Rusdin Rauf, STP., M.P (2016)
Background: Nutritional status is a measure of the condition of a person's body can be seen from the food consumed and the use of nutrients in the body, teenagers who perform daily physical activity in the home tend to have more nutrition for. cause the body less energy issue, if the excess energy intake without balanced physical activity are balanced then the adolescent is overweight. Various facilities for adequate cause motion and activity becomes increasingly restricted and live more relaxed because everything is already available Objective: To determine the relationship of physical activity and nutritional status of young women in Pondok Pesantren Ta'mirul Islam Surakarta. Methods: This study was observational with cross sectional approach. The subjects were 54 female students of class X and XII Ta'mirul Surakarta Islamic Boarding School. Technical data collection identity of respondents with charging Form. Physical activity data using a form of physical activity and nutritional status using anthropometric measurements. Data analysis using Spearman Rank test and test data normality using Kolmogorof Smirnov test. Result: students who have mild physical activity 70.3%, 18.5% moderate physical activity and physical activity weight of 11.1%. Analytic test results obtained there is a relationship of physical activity and nutritional status of young women in Pondok Pesantren Ta'mirul Islam Surakarta. Conclusion: There is a relation of physical activity to the nutritional status of adolescents with value (p = 0.005) in adolescent girls boarding school in Surakarta Islamic Ta'mirul.